THE PORTRAYAL OF BLACK FEMINISM IN GARY GRAY'S SET IT OFF THROUGH CRITICAL RACE THEORY - Sagita, Romala; Zulferdi, Lazuar Azmi; Prihatika, Yusrina Dinar (Pengkajian Amerika, Universitas Gadjah Mada, 2024)
Stories in films are based on social realities in people's lives, embedding messages behind them. Each film is packed with unique characters, events and issues reflecting aspects of life from a particular perspective. One of which is the principles of black feminism in the main characters and to analyze how economic and racial factors influence the character's decision to confront existing injustices depicted in Gary Grey’s Set It Off (1996). The method used is a qualitative research method. Data collection is conducted to sort and understand the research topic by using data from scenes, dialogues, words, and phrases obtained from the film. The main theories used in this research are the Critical Race theory by Kimberlé Crenshaw and the Feminist Economics theory by Marilyn Waring. The findings reveal that the film encompasses principles of black feminism such as racial discrimination, sexism and social class which are portrayed by each main character in the film. This article also depicts the influence of economic and racial factors on the character's decisions in confronting existing injustices. Analyzing this film aims to trigger and enrich the analysis of how films depict the struggle of black women with various problems, especially racial and economic issues.